Pengetahuan dan Motivasi Meningkatkan Penggunaan Aplikasi Mobile JKN pada Pasien BPJS di Instalasi Rawat Jalan RSD Idaman Banjarbaru - Kanzha Khairunnisa, Salbia Putri; Raziansyah, Raziansyah; Fahriadi, Fahriadi (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
The development of digital health services encourages the use of the Mobile JKN application to enhance access and service efficiency for BPJS participants. However, its utilization remains inconsistent due to limited knowledge of its functions and low motivation to use it. This study examined the relationship between knowledge and motivation with the use of the Mobile JKN application among BPJS patients at the Outpatient Installation of RSD Idaman Banjarbaru in 2025. This study employed a quantitative approach with a cross-sectional design. The population comprised 10,478 BPJS patients, while the sample consisted of 100 outpatient BPJS patients who used the Mobile JKN application during March-April 2025 and were selected using a stratified random sampling technique. Data were obtained using a questionnaire and analyzed with the Spearman Rank test. The results indicated that most respondents had good knowledge (74.0%), high motivation (53.0%), and active use of the Mobile JKN application (80.0%). There was a relationship between knowledge and the use of the Mobile JKN application (p-value = 0.030; r = 0.217), as well as a relationship between motivation and the use of the Mobile JKN application (p-value = 0.006; r = 0.272). This study concluded that although most respondents had good knowledge, high motivation, and active application use, there were still users who had not utilized the application optimally. Therefore, the findings of this study may serve as a consideration for hospital management to expand socialization strategies and digital assistance services in order to support the sustainable use of Mobile JKN.